Influence of Polyethylene Glycol (PEG) in CMC-NH4BR Based Polymer Electrolytes: Conductivity and Electrical Study - Zainuddin, Nur Khalidah; Samsudin, Ahmad Salihin (Makara Journal of Technology, 2017)
The present work was carried with new type and promising polymer electrolytes system by development of carboxyl methylcellulose (CMC) doped NH4Br and plasticized with polyethylene glycol (PEG). The sample was successfully prepared via solution casting with no separation phase and good mechanical properties. The electrical conductivity and thermal conductivity of CMC-NH4Br-PEG based PEs system have been measured by the electrical impedance spectroscopy method in the temperature range of 303–373 K. The highest ionic conductivity gained is 2.48 x 10-3 Scm-1 at ambient temperature for sample contain with 8 wt. % PEG. It can be concluded that the plasticized is accountable for the conductance and assist to enhancing the ionic conductivity of the CMC-NH4Br-PEG electrolyte system. The addition of PEG to the CMC-based electrolyte can enhance towards the cation mobility which is turn increases ionic conductivity. The conductivity-temperature of plasticized BdPEs system was found obeys the Arrhenius relation where the ionic conductivity increases with temperature and activation energy for the ions hopping of the highest conducting PEs system only required small value to migrate. The electrical studies show a non-Debye behaviour of BdPEs based on the analyzed data using complex permittivity, ε* and complex electrical modulus, M* of the sample at different temperature.